Unique pattern of molt leads to low intraindividual variation in feather mercury concentrations in penguins - Brasso, Rebecka (2013)
The authors hypothesized that the catastrophic annual molt of penguins (Sphenisciformes) would lead to reduced intraindividual variation of mercury concentrations in body feathers. While mean mercury concentrations varied significantly among 8 penguin species, intraindividual variability did not differ among species and was 3 times lower than values observed in other seabirds. The findings of the present study suggest that a single body feather collected at random per individual can be adequate to estimate mercury exposure at the population level in penguins.